Comparison of fluid tiltmeter data with long-period seismograms: Surface waves and Earth's free oscillations - Ferreira, A; d'Oreye, N; Woodhouse, J; Zuern, W (2006)
We compare observations of long-period seismic surface waves and free oscillations recorded by high-resolution long-base fluid tube tiltmeters and by nearby broadband seismometers after large earthquakes. The quality of the tiltmeter data is comparable to that of the best horizontal component seismic data, recording some of the gravest free oscillations of the Earth, as well as successive passages of seismic surface waves circling the globe. We compare the observations with theoretical seismograms and with theoretical tilt. The predicted and observed surface wave tilt waveforms are very similar provided that we take into account horizontal acceleration effects on the tiltmeter. Phase and amplitude anomalies between the waveforms are well explained by the theoretical transfer function of the instrument. Likewise, observed horizontal seismograms converted into tilt match the tiltmeter data very well. Long-base fluid tube tiltmeters could potentially contribute to obtain high-quality measurements of the long-period seismic spectrum. Copyright 2006 by the American Geophysical Union.